Analysis of Factors Affecting Field Applicability and Long-Term Performance Analysis of LCP Woven Geotextile for Soft Ground Reinforcement - Yu Yan; Wangyu Hahm; Seunghyun Kim; Jiho Youk; Hanyong Jeon (Applied Sciences, 2022)
In recent years, natural disasters have been increasing worldwide due to rapid climate change, and the damage to ground structures is increasing due to the destruction of the ground. Damage to the ground structure can be reduced or eliminated by using LCP woven geotextiles as ground reinforcement. Therefore, in this study, the tensile properties, reduction factor affecting long-term performance, creep behavior, and fatigue properties of LCP woven geotextile were tested and analyzed. As a result, in the case of tensile properties, the maximum tensile strength of the LCP woven geotextile was 192.94 kN/m2 in the MD direction, and it was generally constructed so that the load was transmitted. The total reduction factor is 1.86, which could be applied within 53.8% of the design strength when applied to the field. In addition, it was considered that the effect of the reduction factor for creep deformation on the long-term performance was dominant. Through the analysis of the creep behavior and fatigue characteristics, considering that the creep limit strain was 10%, if an earthquake occurred after 50 years of construction, it can be predicted that up to 90% of UTS would exhibit seismic performance. When LCP woven geotextile was applied as reinforcement, if the cyclic load due to fatigue failure was less than 478,000 times per year, it was considered that there was little possibility of the collapse of the ground structure.